2020
DOI: 10.2147/cmar.s267523
|View full text |Cite
|
Sign up to set email alerts
|

<p>Neutrophil-to-Lymphocyte Ratio and Its Changes are Related to Grade II–IV Glioma Recurrence</p>

Abstract: Objective: To explore whether the neutrophil-to-lymphocyte ratio (NLR) and its changes are related to tumor recurrence in grade II-IV glioma patients. Methods: One hundred patients who underwent two surgeries (first for diagnosis and the second for recurrence) were retrospectively analyzed. Complete blood count was obtained preoperatively before any treatment. Basic NLR (before the first surgery) and NLR changes were calculated. Tumor recurrence was evaluated by progression-free survival (PFS) using the Kaplan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…However, we demonstrated that the pretreatment H-NLR values were independently associated with significantly diminished OS times (63.0 vs 90% at 6-months) compared with their L-NLR counterparts. Recently systemic inflammationrelated indices have been shown to accurately predict poorer prognoses in GBM patients either measured at the time of diagnosis, after initial neurosurgery, before the adjuvant therapy and before SNS in relapsed patients [16][17][18][19][23][24][25][26][27][28][29]. However, to our best information, there were no data in the comparative literature for R-GBM patients who underwent salvage BEVIRI during the preparation of this manuscript.…”
Section: Discussionmentioning
confidence: 91%
“…However, we demonstrated that the pretreatment H-NLR values were independently associated with significantly diminished OS times (63.0 vs 90% at 6-months) compared with their L-NLR counterparts. Recently systemic inflammationrelated indices have been shown to accurately predict poorer prognoses in GBM patients either measured at the time of diagnosis, after initial neurosurgery, before the adjuvant therapy and before SNS in relapsed patients [16][17][18][19][23][24][25][26][27][28][29]. However, to our best information, there were no data in the comparative literature for R-GBM patients who underwent salvage BEVIRI during the preparation of this manuscript.…”
Section: Discussionmentioning
confidence: 91%
“…Most glioma patients have a strong neutrophilia 143 , 144 , and neutrophil infiltration at the tumor site has been associated with decreased overall survival (OS), tumor recurrence in grade 2–4 glioma patients and brain metastasis 145 . Circulating neutrophils are recruited at the tumor site by CXCL8 produced by FasL triggering on glioma cells 146 , 147 or by the Migration Inhibitory Factor (MIF) produced by glioma cancer stem cells 148 .…”
Section: Discussionmentioning
confidence: 99%
“…12-14 Moreover, neutrophil counts have previously been associated with the prognosis of glioma patients. [15][16][17][18] NETs have been recently reported in glioma tissues and their expression was correlated with glioma grades. 19,20 In our study, plasma levels of NETs were detected in glioma patients.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] Neutrophil counts have previously been associated with the prognosis of glioma patients. [15][16][17][18][19] Neutrophil extracellular traps (NETs) have been recently reported in glioma tissues and their expression was correlated with glioma grades. 20 NETs are web-like DNA-containing structures released from activated neutrophils, which are comprised of decondensed chromatin and proteases such as myeloperoxidase (MPO) and neutrophil elastase (NE).…”
Section: Introductionmentioning
confidence: 99%